2017
DOI: 10.1080/19390211.2017.1343889
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of L-Arginine and Vitamin E Against Bone Loss Induced by Nano-Zinc Oxide in Rats

Abstract: The purpose of this study was to illustrate the effects of zinc oxide nanoparticles (ZnO-NPs) administration on bone turnover and bone resorbing agents in rats and how L-arginine (L-arg) or vitamin E (vit E) co-administrations might affect them. Fasting rats were randomly divided into four groups (n = 10): G1-normal healthy animals; G2-ZnO-NPs-exposed rats (600 mg/kg1/day); G3-ZnO-NPs-exposed rats co-administrated L-arg (200 mg/kg1/day); G4-ZnO-NPs-exposed rats co-administrated vit E (200 mg/kg1/day). The ingr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…However, Abdelkarem et al reported that serum levels of Ca and P did not significantly differ when rats were dosed with 600 mg/kg ZnO NPs for 5 days by oral administration. 10 Herein, we found that increasing the duration of administration may increase the possibility of damage to the bone tissue. Thus, we believe that ZnO NPs disrupt the balance of bone metabolism and promote osteoclast activity.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, Abdelkarem et al reported that serum levels of Ca and P did not significantly differ when rats were dosed with 600 mg/kg ZnO NPs for 5 days by oral administration. 10 Herein, we found that increasing the duration of administration may increase the possibility of damage to the bone tissue. Thus, we believe that ZnO NPs disrupt the balance of bone metabolism and promote osteoclast activity.…”
mentioning
confidence: 95%
“…In China, each child whose height is two standard deviations less than the mean height of children of the same sex, age, and race are considered to have a short stature. 10 The age-standardized prevalence of short stature is 3.70% in China. 11 A number of studies have found that short stature may affect the physical and mental health of children, especially boys.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 NPs are widely applied in industry, cosmetics, and food products. 15,16 As a trace element, zinc participates in various metabolic processes. A substantial proportion of zinc (~30%) is stored in bone, and the pathological reduction of zinc levels impairs bone growth.…”
Section: Introductionmentioning
confidence: 99%
“…The bone protecting effects of vitamin D are well known, but also other compounds, such as vitamin C, B12 and folates seem to exert beneficial anti-inflammatory and metabolic effects on bone health. Both L-arginine and vitamin E coadministration reduces TNF-α and IL-6 levels induced by zinc oxide nanoparticle administration in rats, counteract its deleterious effects on bone turn over [ 84 ]. Tart cherry (Prunus cerasus), a fruit rich in polyphenols, such as flavonols, hydroxycinnamic acids, proanthocyanidins and anthocyanidins, has been reported to display antioxidant and anti-inflammatory properties and could be used as a supplement to prevent inflammation-mediated bone loss in TNF-overexpressing transgenic mice [ 85 ].…”
Section: Small Molecules Nanoparticles and Natural Productsmentioning
confidence: 99%